Kepemimpinan Kepala Sekolah dalam Peningkatan Mutu Sekolah Melalui Pengawasan Proses Belajar Mengajar (Studi Kasus: di SMPN 26 Baru Kota Malang) - Sudari Sudari (IKIP Budi Utomo Malang, 2016)
Headmaster leadership is the determinant of the school future. The very prominent role and important by headmaster is the learning supervision role. This research aimed at knowing the headmaster leaderships style of SMPN 26 (State Junior High School 26) of Malang city in improving the education quality, knowing the headmaster role of SMPN 26 of Malang City in implementing the supervision role to improve the learning process in school, knowing the supporting and inhibiting factors of the headmaster of SMPN 26 of Malang city in implementing the supervision role in improving the learning process in school. Data were collected by document analysis, observation and depth interview to 5 teachers, vice headmaster of curriculum, vice headmaster, public relations staffs, headmaster, and were analyzed with descriptive qualitative approach technique. Based on data analysis , showed that ( 1 ) headmaster leadership style of SMPN 26 of Malang city tend to use democratic participative leadership and authoritarian leadership style in urgent condition ( 2 ) the headmaster role of SMPN 26 of Malang city in improving the learning process by giving intensive cultivation to the teachers through individual supervision, direct class observation ( 3 ) the implementation of direct class supervision observation was influenced by external factors,either supporting or inhibiting factors.